2016
DOI: 10.1186/s12967-016-1026-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on host immune response and survival in melanoma: an analysis of 3 patient cohorts

Abstract: BackgroundAge has been reported as an independent prognostic factor for melanoma-specific survival (MSS). We tested the hypothesis that age impacts the host anti-tumor immune response, accounting for age-specific survival outcomes in three unique melanoma patient cohorts.MethodsWe queried the U.S. population-based Surveillance, Epidemiology, and End Results Program (SEER), the prospective tertiary care hospital-based Interdisciplinary Melanoma Cooperative Group (IMCG) biorepository, and the Cancer Genome Atlas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
(38 reference statements)
1
25
1
Order By: Relevance
“…We are aware that our findings do not necessarily reflect immune responses at the tumor site in melanoma patients. Brisk tumor-infiltrating lymphocytes and high lymphocyte tumor distribution and density in melanoma are associated with improved disease-specific survival [ 29 ]. A study with tumor tissue samples from 147 metastatic melanoma patients showed an independent positive association between overall survival and higher counts of CD8+ T cells and PD-1 expressing cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that our findings do not necessarily reflect immune responses at the tumor site in melanoma patients. Brisk tumor-infiltrating lymphocytes and high lymphocyte tumor distribution and density in melanoma are associated with improved disease-specific survival [ 29 ]. A study with tumor tissue samples from 147 metastatic melanoma patients showed an independent positive association between overall survival and higher counts of CD8+ T cells and PD-1 expressing cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progressive impairment of both innate and adaptive immunity affects responses to pathogens, and vaccines as wells as anti-tumour surveillance [ 84 ]. Evidence of an aging-related T-cell dysfunction has been recently reported in gene-expression studies of different melanoma-patient cohorts [ 85 ]. Tumour-infiltrating lymphocytes (TILs) in primary melanoma represent a known pathological, albeit surrogate, marker of the host anti-tumour immune response.…”
Section: Cutaneous Melanoma Of the Elderlymentioning
confidence: 99%
“…Older patients tend to present with primary tumors with aggressive features and have an overall poorer prognosis when compared to younger patients (Balch et al, ; Cavanaugh‐Hussey, Mu, Kang, Balch, & Wang, ; Hoag et al, ). Age‐related comorbidities, weakening immunity, and delivery of care may be partly contributing to this trend (Rees et al, ; Weiss et al, ). Here, we use a population‐based case–control study with 20‐year survival data to investigate characteristics that are associated with melanoma survival in older patients (those 56 years or older) compared to younger patients (those <56 years).…”
Section: Introductionmentioning
confidence: 99%